NILAI-NILAI KEMANUSIAN DALAM PENDIDIKAN ANAK USIA DINI INKLUSI - Suhendro, Eko; Syaefudin, Syaefudin (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2020)
This study aims to analyze and map inclusive education for children who have special intelligence potential. And to find out whether the inclusive PAUD teacher has applied the concept of education that prioritizes the humanitarian side or not. This type of research is qualitative. Using an educational sociology approach. Data collection was obtained through literature analysis studies. Data analysis techniques used are data reduction, data display, data verification, and affirmation of conclusions. An important finding in this research is the existence of human values possessed by every educator, in positioning themselves as a facilitator for children with special needs. The conclusion in this study is that teachers in PAUD inclusion must have human values, which include: a) Awareness that all children are born the same, b) Educate professionally, c) Look at children with special needs that are special, d) Educate because they care, e ) Educate with love, f) Educate through example.